ANALISIS PENERAPAN COST REDUCTION DALAM PENINGKATAN LABA - Iqbal Nikmatullah, Mohamad; Widarsono, Agus (Program Studi Akuntansi FPEB UPI, 2014)
This research purpose to know how application of Cost Reduction within increase profit PD. Bank Perkreditan Rakyat in West Java based on one of Cost Reductiontools is Fixed Cost Analysis. This research method usedÂ descriptive quantitative. The sampling technique using non-probability sampling with purposive sampling approach with criteria (1) PD BPR in West Java publishes financial report in Bank Indonesia for three years; (2) PD BPR good categorized according to the ratio of capital adequate ratio (CAR); (3) PD BPR has positive ratio return on asset (ROA); (4) PD BPR with total assets of more than the average total assets PD BPR in West Java. The results showed that the average value of fixed cost ratio from year to year has decline, it's inversely with the value of earnings from year to year increase. It shows that the efficiency carried out use fixed cost aset affect to profitability. The proportion of lower fixed cost give opportunities for PD BPR to reach more income than expenditure variable, while result the breakeven analysis showed absence of effective implementation of cost reduction in the interest sector BPR was indicated by the absence of a link between the growth rate of the increase in profit spread.